The Effect of Social and Economic Factors on Maternal Mortality in Provinces of Iran within 2009-2013 - Hanie Gholampoor; Abolghasem Pourreza; Hasan Heydari (Shahid Sadoughi University of Medical Sciences, 2018)
Background: The mothers' role in health of family members is very important, and her death has uncompensable losses for the family and society. With regard to the importance of maternal mortal ratio in development indicators of the United Nations (UN) this study is conducted to investigate the impact of socioeconomic factors on maternal mortality ratio Methods: In the current study the role of socioeconomic factors on maternal mortal ratio was investigated by panel regression. Data include number of maternal mortality, total fertility, number of hospital beds, number of midwifes, number of physicians and urbanization in the period between 2008 and 2012. Since the dependent variable was in count form, Poisson estimator, Hausman test, and Breusch-pagan test were used. Results: Based on the findings, household's income and fertility rate had direct and inverse association with maternal mortality, respectively. Investigating the association between midwifes and maternal mortality showed that increasing the number of midwifes decrease it, but no significant association was found between the number of physicians and maternal mortality. Number of hospital beds also showed a direct association (significant at 10%). Conclusion: All of the variables to somehow are related with the level of development. In developed regions, per capita income, access to health resource and urbanization is higher and there is more equity in distribution of health resources. It could be concluded from the findings that by increasing the level of development, maternal mortality would decrease.